Territorial mobility and subsistence strategies during the Ebro Basin Late Neolithic-Chalcolithic: A multi-isotope approach from San Juan cave (Loarre, Spain) - Villalba Mouco, Vanessa (2018)
The use of isotopic analysis in human and animal remains from the Holocene has proved to be a very useful tool to explore the exploitation and adaptation of past populations to different environments. In this study we present isotopic analysis results of carbon, nitrogen and strontium from the Late Neolithic-Chalcolithic site of San Juan cave (Loarre, Spain). We analysed 33 humans, divided in adult and subadult groups, and 16 animals recovered from the same archaeological context. Stable isotope analysis of carbon and nitrogen has allowed to distinguish an homogeneous subsistence pattern during the Late Neolithic-Chalcolithic transition. The use of strontium isotopes (87Sr/86Sr) in human dental enamel suggests 19% (4 out of 21) are non-local individuals, based on comparison with the local bioavailable 87Sr/86Sr range calculated using microfauna teeth from the archaeological context, modern plants and snails. This new study gives information about Late Neolithic communities located in the north-east of the Iberian Peninsula, and it allows inference of the socio-economic structure, territorial mobility and individual provenance of humans.